FACTORS INFLUENCING EMPLOYEE’S TURNOVER INTENTION : A STUDY ON FIVE STAR HOTEL EMPLOYEES IN THE RIYADH CITY OF SAUDI ARABIA - Abdullah, AlkhalielAdeeb (The journal of contemporary issues in business and government, 2021)
The employee‘s turnover is mostly arise in the hotel industries due to the lack of training, poor remuneration, job stress, and the incapability of the management. It is the decision of the employees to continue with their service by taking into consideration of the factors such as job satisfaction, working atmosphere, training and development, promotional prospects offered by the management. The population of the study includes 266 working staff in five star hotels in Riyadh city. the structural relationship of factors influencing the turnover of hotel employees shows out of the eleven factors, eight of them having the significance value P<0.001, and two of the constructs with the significance value of P<0.05. The study depicts that, the factors such as employee expectation, job stress, remuneration, motivation, promotion, training and development, interpersonal relationship and work atmosphere had signiﬁcant positive influence on employee turnover.